Changes in Distortion Product Otoacoustic Emission Components after Music Exposure. - Torre III, Peter; Grace, Jennifer (Journal of the American Academy of Audiology, 2014)
Background: Young adults experience some type of recreational noise exposure on a daily basis; this includes using personal music (PM) systems with earphones. In most cases, this exposure is intermittent and the short-term effects of this exposure on the auditory system are becoming better understood. Purpose: The purpose of this study was to examine the effects of one hour of music exposure using a PM system on distortion product otoacoustic emission (DPOAE) absolute levels and generator and characteristic frequency (CF) component levels. Study Samples: Young adults (n = 101) between 18-30 years with normal hearing participated listened to one hour of music through earphones. A second group of young adults (n = 21) served as controls and did not listen to music, but sat in the sound-treated room for one hour. Data Collection and Analysis: Otoscopy, tympanometry, and a hearing screening (≤20 dB HL at 0.5,1, 2, and 4 kHz) were completed in a randomly determined test ear. Preferred listening level, in dBA, was obtained and DPOAEs (2f1-f2) were measured between 1 and 6 kHz with stimulus levels fixed at L1,L2 = 55,40 dB SPL. Absolute DPOAE levels, along with generator and CF components levels were measured before and after each participant listened to one hour of music at their preferred level in a quiet setting. For data analyses, absolute DPOAE and generator and CF component levels were collapsed into 1/3rd octave bands centered around 1, 1.5, 2, 3, 4, and 6 kHz. Results: Mean preferred listening level was 57.8 dBA, with males having a higher mean level of 61.1 dBA compared with females who had a mean level of 55.7 dBA. Females and males had negligible mean changes in absolute DPOAE levels at 1,1.5, and 2 kHz, but males had 0.4-1 dB mean decreases after music at 3,4, and 6 kHz compared to females, although not statistically significant. For DPOAE generator component data, females had small mean decreases for the two lower frequencies whereas males had mean decreases of 0.4-0.8 dB at 3, 4, and 6 kHz. Because of missing data, analyses of the CF component were limited, although females had small mean decreases at four frequencies while males had small mean decreases at two frequencies. There was no effect of listening to music on changes in DPOAEs but control participants had strong reliability (i.e., little or no change) after sitting in quiet for one hour. Conclusions: Young adults listened to music well below what would be considered hazardous. Because of the lower listening levels, DPOAEs showed very little change after music. Although there were no significant short-term changes in DPOAEs after music, the cumulative effect of this noise exposure is still unknown.